Hybrid control of a parallel platform based on pneumatic artificial muscles combining sliding mode controller and adaptive fuzzy CMAC - Shi, G.L.; Shen, W. (Control engineering practice, 2013)
A three degree of freedom parallel platform based on pneumatic artificial muscle (TDOFPPM) with obvious features of nonlinearity, uncertainty and coupling is introduced in this paper. It would be a challenge to control a nonlinear system with strong uncertainties. The complexity of air flow and the hysteresis of pneumatic artificial muscle are the main uncertainties in the TDOFPPM system. A hybrid controller combining sliding mode controller and adaptive fuzzy CMAC (AFCMAC) uncertainty compensator has been proposed for TDOFPPM. In order to guarantee the approximation ability for those main uncertainties, the input space and parallel structure are carefully designed for AFCMAC compensator. Finally a TDOFPPM experiment facility is introduced and the posture tracking control of TDOFPPM under two reference input signals are presented. The experiment results indicate the performance of hybrid controller is favorable.